Fabrication of viable centimeter‐sized 3D tissue constructs with microchannel conduits for improved tissue properties through assembly of cell‐laden microbeads. (3rd July 2012) - Luo, Houyong; Chen, Maiqin; Wang, Xiu; Mei, Yang; Ye, Zhaoyang; Zhou, Yan; Tan, Wen‐Song
Abstract Bottom‐up approaches have emerged as a new philosophy in tissue engineering, enabling precise control over tissue morphogenesis at the cellular level. We previously prepared large bone‐like tissues using cell‐laden microbeads (microtissues) by following a modular approach to ensure cell viability. However, a long‐term culture of such avascular macroscopic tissues (macrotissues) has not been evaluated. In the present study, microtissues were fabricated by cultivating human fibroblasts on Cytopore‐2 microbeads in spinner flasks for 16 days. We then examined the long‐term perfusion culture for macrotissues. Specifically, following assembly in a perfusion chamber for 15 days, cell death was found to be prominent at a depth of 500 µm from the surface of macrotissues towards the interior, suggesting that there was a new mass transfer limit leading to cell death instead of tissue maturation. Subsequently, we developed a strategy by incorporating microchannel structures in centimeter‐sized tissue constructs to promote mass transport. By installing glass rods (1 mm diameter, 1 mm wall‐to‐wall spacing) in the perfusion chamber, stable microchannel architectures were introduced during the microtissue assembly process. Based on live/dead assay and scanning electron microscopy (SEM), these channelled macrotissues (length × diameter, 1.6 × 2.0 cm) demonstrated high cell viability and compact packing of microbeads. Comparative biochemical analysis further suggested a more homogeneous spatial distribution of cells and extracellular matrix (ECM) in the channelled macrotissues than in solid ones. Viable 3D large tissues can therefore be prepared by assembling cell‐laden microbeads in conjunction with microchannel carving, meeting clinical needs in tissue repair. Copyright © 2012 John Wiley & Sons, Ltd.